APPLICATION OF SPATIAL TECHNIQUES IN GEOGRAPHIC INFORMATION SYSTEMS FOR THE EXPLORATION OF EPITHERMAL GOLD DEPOSIT POTENTIAL IN THE WESTERN PART OF JAVA ISLAND, INDONESIA - Humaira, Sarah
This study was conducted to explore the potential for epithermal gold deposits in the western part of Java Island, Indonesia, using spatial techniques in geographic information systems. The background of this research is based on the high global demand for gold and the significant potential that Indonesia, particularly Java Island, possesses, which has not been optimally utilized. The study aims to produce a potential map for epithermal gold mineralization based on geochemical, geological, and structural analyses using the fuzzy logic method. This study used regional geological data, geochemical data, and digital elevation model (DEM) as the main basis for analysis. Geochemical data were analyzed to understand the distribution of elements associated with epithermal gold, namely Cu and Zn. Geological data were processed to classify rock lithology and understand the geological structures controlling the presence of gold deposits. DEM was used to analyze the topography and lineament correlated with geological structures. The results of this analysis produced a prospectivity map that divides the study area into zones of very high, high, low, and very low prospectivity.